HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN PENGALAMAN MENJADI RELAWAN DENGAN KEMAUAN MELAKUKAN RJP SEBAGAI PENANGANAN OHCA DIMASA PANDEMI COVID-19 PADA MAHASISWA S1 KEPERAWATAN DAN KSR UPN VETERAN JAKARTA - Stephanie Ester Rosalia Sitorus, (2021)
Cardiac arrest is a disruption of circulation function accompanied by an irregular heartbeat due to damage to the heart's electricity. Patients with COVID-19 symptoms were less likely to receive bystander-CPR when compared to patients who were not diagnosed or suspected of being positive for COVID-19. This cross-sectional study with the distribution of questionnaires conducted online involved 130university students to measure the level of knowledge and experience of respondents as volunteers with the level of willingness to perform CPR. With the result that there is no relationship between respondent characteristics and willingness to perform CPR before and during the COVID-19 pandemic, it is indicated by a P-Value > 0.05; There is no relationship between the level of knowledge of CPR and the willingness to perform CPR before (P-value = 0.812) and during (p-value = 0.478) the COVID-19 pandemic; There is a relationship between the experience of being a volunteer and the willingness to perform CPR before (P-value = 0.014) and during (P-value = 0.019) the COVID-19 pandemic.